Implementation of Tawheed Learning Using the Book of Aqidatul Layman in Class 3 of Cahaya Cendekia Glagah Elementary School - Hosniati; Ainur Rofiq Sofa (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2026)
This study aims to examine the implementation of tauhid learning using the Aqidatul Awam book in Grade 3 at SD Cahaya Cendekia Glagah, focusing on lesson planning, learning implementation, and the teaching methods and strategies employed by teachers. A qualitative research approach with a descriptive design was applied to obtain an in-depth understanding of the learning process in its natural context. Data were collected through classroom observations, semi-structured interviews with teachers, students, and school administrators, as well as documentation analysis. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that tauhid learning was planned systematically and adapted to students’ cognitive and developmental characteristics. The learning implementation was conducted gradually, repetitively, and contextually through the recitation and explanation of nazham, supported by simple examples related to students’ daily lives. The teaching methods and strategies, including simple lectures, memorization, question-and-answer sessions, and habituation, effectively supported both cognitive understanding and the development of religious attitudes. This study concludes that the integration of classical Islamic texts with student-centered instructional approaches can effectively strengthen foundational tauhid understanding at the elementary school level.